American Urogynecologic Society Systematic Review: The Impact of Weight Loss Intervention on Lower Urinary Tract Symptoms and Urinary Incontinence in Overweight and Obese Women. Issue 4 (April 2020) - Yazdany, Tajnoos; Jakus-Waldman, Sharon; Jeppson, Peter C.; Schimpf, Megan O.; Yurteri-Kaplan, Ladin A.; Ferzandi, Tanaz R.; Weber-LeBrun, Emily; Knoepp, Leise; Mamik, Mamta; Viswanathan, Meera; Ward, Renée M.
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2020;26:16–29) Urinary incontinence (UI) affects many women across the world and can have severe impacts on quality of life. Obesity has been reported to play a role in the development of UI.